Earnings Persistence and Abnormal Audit Fees - Xiaohui Zhou; Pengzheng Lou; Yongmin Wu; Lijuan Zhang (Discrete Dynamics in Nature and Society)
This study discusses the impact of earnings persistence on abnormal audit fees and explores the mechanism between earnings persistence and abnormal audit fees. The results show that the stronger the earnings persistence is, the lower the abnormal audit fees are. The earnings persistence only has a significant impact on the positive abnormal audit fees, and the impact on the negative abnormal audit fees is not obvious. Furthermore, it is found that the negative correlation between the earnings persistence and abnormal audit fees has obvious heterogeneity; that is, it is more significant in companies with low environmental uncertainty and state-owned companies. The mechanism test shows that earnings persistence reduces abnormal audit fees by improving company operating risk, which proves the “Risk Compensation View” of abnormal audit fees to a certain extent. The research provides an important reference for the management and shareholders to eliminate abnormal audit fees and for the regulatory authorities to regulate audit fees.